2005
DOI: 10.1111/j.1349-7006.2005.00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental trial for diagnosis of pancreatic ductal carcinoma based on gene expression profiles of pancreatic ductal cells

Abstract: Pancreatic ductal carcinoma (PDC) remains one of the most intractable human malignancies, mainly because of the lack of sensitive detection methods. Although gene expression profiling by DNA microarray analysis is a promising tool for the development of such detection systems, a simple comparison of pancreatic tissues may yield misleading data that reflect only differences in cellular composition. To directly compare PDC cells with normal pancreatic ductal cells, we purified MUC1-positive epithelial cells from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 21 publications
1
56
0
Order By: Relevance
“…Moreover, when we split the series to assess survival of patients with above or below median CHCHD4 expression, we found that CHCHD4 expression above the median was associated with a significantly poorer survival outcome (P = 0.016, log-rank test; Figure 6C). Confirming these findings, analysis of the microarray data from 3 independently published studies (35)(36)(37) showed that CHCHD4 expression was higher in pancreatic cancer compared with that in normal pancreatic tissue ( Figure 6D), and in breast cancer, increasing CHCHD4 expression correlated with increasing tumor grade ( Figure 6E). Furthermore, analyses of CHCHD4 expression in glioma (37) showed that increasing CHCHD4 expression correlated with increasing tumor grade ( Figure 6F) and reduced survival ( Figure 6G).…”
Section: Chchd4 Encodes 2 Alternatively Spliced and Differentially Exmentioning
confidence: 57%
See 2 more Smart Citations
“…Moreover, when we split the series to assess survival of patients with above or below median CHCHD4 expression, we found that CHCHD4 expression above the median was associated with a significantly poorer survival outcome (P = 0.016, log-rank test; Figure 6C). Confirming these findings, analysis of the microarray data from 3 independently published studies (35)(36)(37) showed that CHCHD4 expression was higher in pancreatic cancer compared with that in normal pancreatic tissue ( Figure 6D), and in breast cancer, increasing CHCHD4 expression correlated with increasing tumor grade ( Figure 6E). Furthermore, analyses of CHCHD4 expression in glioma (37) showed that increasing CHCHD4 expression correlated with increasing tumor grade ( Figure 6F) and reduced survival ( Figure 6G).…”
Section: Chchd4 Encodes 2 Alternatively Spliced and Differentially Exmentioning
confidence: 57%
“…Overexpression of HIF-α occurs in many human cancers and correlates with increased hypoxia, angiogenesis and metastasis, treat- ) analyzed from gene expression profiling data described previously (35). P = 0.005.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Third, published microarray studies reveal frequent alteration (both up-and downregulation) of RABL6A mRNA levels in PDAC tumors. [13][14][15][16] In this study, we evaluated RABL6A expression levels in human PDAC cell lines and in resected PDAC tumors from patients and correlated the latter with clinicopathological variables and survival. We also assessed how its depletion affected pancreatic cancer cell growth, survival, and responsiveness to PDAC chemotherapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, pancreatic adenocarcinoma tissues contain a significant amount of adjacent normal tissue. 32,33 Because of this, our candidate pancreas markers were enriched for genes elevated in pancreas adenocarcinoma relative to normal pancreas cells. As a result of this approach, we identified a novel pancreas cancer-specific marker, coagulation factor V (F5).…”
Section: Marker Candidate Selectionmentioning
confidence: 99%